2008
DOI: 10.1182/blood-2007-08-107292
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CS1 humanized monoclonal antibody HuLuc63 inhibits myeloma cell adhesion and induces antibody-dependent cellular cytotoxicity in the bone marrow milieu

Abstract: Currently, no approved monoclonal antibody (mAb) therapies exist for human multiple myeloma (MM). Here we characterized cell surface CS1 as a novel MM antigen and further investigated the potential therapeutic utility of HuLuc63, a humanized anti-CS1 mAb, for treating human MM. CS1 mRNA and protein was highly expressed in CD138-purified primary tumor cells from the majority of MM patients (more than 97%) with low levels of circulating CS1 detectable in MM patient sera, but not in healthy donors. CS1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
501
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 441 publications
(520 citation statements)
references
References 32 publications
12
501
1
6
Order By: Relevance
“…14 In preclinical myeloma xenograft models involving mice, elotuzumab demonstrated dose-dependent antitumor activity via ADCC. 15 Furthermore, elotuzumab in combination with lenalidomide (an IMiD) and bortezomib (a PI) enhanced ADCC in vitro, potentially mediated through enhancement of natural killer cell activity. 6,[15][16][17] On November 30, 2015, the US Food and Drug Administration approved the three-drug combination of elotuzumab plus lenalidomide and dexamethasone for use in patients with MM who had received 1-3 prior therapies, based on the positive results of the ELOQUENT-2 study (NCT01239797).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 In preclinical myeloma xenograft models involving mice, elotuzumab demonstrated dose-dependent antitumor activity via ADCC. 15 Furthermore, elotuzumab in combination with lenalidomide (an IMiD) and bortezomib (a PI) enhanced ADCC in vitro, potentially mediated through enhancement of natural killer cell activity. 6,[15][16][17] On November 30, 2015, the US Food and Drug Administration approved the three-drug combination of elotuzumab plus lenalidomide and dexamethasone for use in patients with MM who had received 1-3 prior therapies, based on the positive results of the ELOQUENT-2 study (NCT01239797).…”
Section: Introductionmentioning
confidence: 99%
“…15 Furthermore, elotuzumab in combination with lenalidomide (an IMiD) and bortezomib (a PI) enhanced ADCC in vitro, potentially mediated through enhancement of natural killer cell activity. 6,[15][16][17] On November 30, 2015, the US Food and Drug Administration approved the three-drug combination of elotuzumab plus lenalidomide and dexamethasone for use in patients with MM who had received 1-3 prior therapies, based on the positive results of the ELOQUENT-2 study (NCT01239797). 4,18 Approval by the European Medicines Agency followed in May 2016 for adult patients with MM who had received one or more therapies.…”
Section: Introductionmentioning
confidence: 99%
“…In a separate analysis, low but detectable levels of soluble SLAMF7 (sSLAMF7) were found in the sera of some patients with multiple myeloma, while sSLAMF7 was not present in healthy donor sera [40]. Although there was no correlation between SLAMF7 surface expression and disease stage, patients with advanced stage or symptomatic multiple myeloma (International Stage Systems [ISS] II/III) had significantly higher levels of sSLAMF7 than those with ISS I, suggesting that sSLAMF7 may represent a biomarker of disease progression [40].…”
Section: Preclinical Rationalementioning
confidence: 99%
“…The primary mechanism of action of elotuzumab is the lysis of multiple myeloma cells via ADCC (Figure 1), a process initially thought to be dependent on the presence of NK cells or other peripheral blood mononuclear cells (PBMCs) [39,40]. However, as depletion of T cells, B cells or monocytes from a PBMC effector cell population had no effect on elotuzumab-induced ADCC, it was suggested that the lytic activity of elotuzumab is primarily mediated by NK cells [39].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Clinical trials presented at this meeting included most prominently the final results for the 1703 Phase Ib/II study of elotuzumab in combination with lenalidomide and dexamethasone in patients with relapsed/refractory MM [11] and the interim results of the ASPIRE Phase III trial, which evaluated carfilzomib, lenalidomide and dexamethasone (KRd) versus lenalidomide and dexamethasone (Rd) in patients with relapsed disease [12]. Elotuzumab is mAb that targets SLAMF7, a cell surface glycoprotein that is highly expressed at the surface of plasma cells [13]. The 1703 trial reported data for 73 patients randomized to elotuzumab 10 or 20 mg/kg intravenous in combination with lenalidomide (25 mg) and low-dose weekly dexamethasone (40 mg) with a primary end point of overall response rate (ORR).…”
Section: Novel Therapies and Combinations In The Relapsed And Upfront Setmentioning
confidence: 99%